2007
DOI: 10.1080/17457300701420966
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and geographical heterogeneity in unintentional home injuries incidence rate: new evidence based on Multiscopo Survey in Italy

Abstract: Home injuries together, with road traffic accidents, are estimated to be the third cause of death in Italy (Arokiasamy and Krishnan 1994). However, as in most other countries, in Italy there is a lack of information on home injuries and on how differences in geographical patterns may influence the scope and magnitude of this phenomenon. By analysing a multipurpose large survey (Multiscopo) carried out annually, geographical heterogeneity in home injuries incidence rate can be investigated. The aim of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
2
7
1
Order By: Relevance
“…Similar finding was seen in various studies done by Snidero S et al, Lindblad BE et al and Mohammadi R et al who reported 60.4%, 41% and 43% respectively from various parts of the globe. 9,17,18 In the present study majority of them had their first aid treatment at home itself which is similar to the study done by Gupta RK et al 15 A community -based study on incidence and pattern of injuries among residents of rural area in Nigeria by Olawale OA et al reported that more than half (58%) were treated in government hospital and another study also reported treatment was given at primary care setting. 3 Since domestic accidents results in minor injuries that were negligible or can be treated at home itself, most of the people do not visit health facilities.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Similar finding was seen in various studies done by Snidero S et al, Lindblad BE et al and Mohammadi R et al who reported 60.4%, 41% and 43% respectively from various parts of the globe. 9,17,18 In the present study majority of them had their first aid treatment at home itself which is similar to the study done by Gupta RK et al 15 A community -based study on incidence and pattern of injuries among residents of rural area in Nigeria by Olawale OA et al reported that more than half (58%) were treated in government hospital and another study also reported treatment was given at primary care setting. 3 Since domestic accidents results in minor injuries that were negligible or can be treated at home itself, most of the people do not visit health facilities.…”
Section: Discussionsupporting
confidence: 77%
“…Few studies done by Mittal BN et al and Alptekin F et al reported that kitchen is the second common place of accident next to living room with frequency of 26.7% both. 12,16 A study done by Snidero S et al 9 reported that kitchen was the most frequent place of accidents (52.9%) as in this study. In the present study most frequent site of injury due to domestic accidents was Upper limb and fingers (51%) followed by lower limb and toes (32%).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Unemployment has been shown to be linked to burns and home injuries; 7 , 37 unfortunately, no individual-level studies on unemployment and non-fatal all-cause injuries in adults have been found.…”
Section: Discussionmentioning
confidence: 99%
“…12,16 A study done by Snidero et al reported that kitchen is the most frequent place of accidents (52.9%) as in this study. 17 Consequently in our study, a significant statistical association was found between extreme age groups, female sex, occupation as homemaker and occurrence of domestic accidents. Mostly the accidents were observed in families with more than 4 rooms and there was no significant statistical association between family type, family size, type of housing and occurrence of domestic accidents.…”
Section: Discussionmentioning
confidence: 70%